Gavin & Stacey. Season one [videorecording (DVD)] - Dowd, Ted; Corden, James; Jones, Ruth, 1966- (BBC Video ; Distributed by BBC Worldwide Americas ; Distributed by Warner Home Video, 2009)
Gavin and Stacey speak every day on the phone at work, and yet they've never met ... until now. Gavin is an ordinary boy from England. Stacey is an ordinary girl from Wales. When Gavin and Stacey finally meet, the peculiar personalities of their families and friends guarantee that there will be no such thing as 'ordinary' ever again.